Teacher Strategies for Creating Interesting and Dynamic Learning - Kinanti, Ratna Ayu; Hernawan, Asep Herry (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research discusses the key role of teachers in creating interesting and dynamic learning. Many elementary school teachers still use the lecture method in learning, so learning becomes monotonous and unpleasant for elementary school students, especially at SD Negeri Pinayungan II, the subject of this research. To improve the quality of education, teachers need to develop various strategies that can make learning more interesting for students. This research aims to inspire teachers, educators, and educational practitioners to improve the effectiveness of their teaching so that they can create more interesting and dynamic learning for students. The research approach used is qualitative with a case-based method regarding teacher strategies for creating interesting and enjoyable learning. The data collection technique uses interview, observation, and documentation techniques. Data analysis techniques in this study use qualitative descriptive analysis techniques. The research results using interview, observation, and documentation techniques showed that many teachers used the lecture method, making students disinterested in learning. There are many strategies that teachers can use to make learning in the classroom interesting and dynamic, namely by using strategies such as educational technology, applying a variety of teaching methods, and so on. Teachers must innovate by trying interesting and dynamic strategies to achieve this.